1964
DOI: 10.1021/je60020a007
|View full text |Cite
|
Sign up to set email alerts
|

Binary Vapor-Liquid Equilibria Involving 1,2-Dichloroethane and 1,1,1- and 1,1,2-Trichloroethane.

Abstract: Vapor-pressure equilibrium data for three binary systems: 1,2-dichloroethane-l, 1,1trichloroethane, 1,2-dichloroethane-l, 1,2-trichloroethane, and 1,1,1-and 1,1,2-trichlorethane were obtained. The activity coefficients for these systems deviated only slightly from the ideal. Some thermodynamic inconsistencies were noted.ChLORINATION of ethylene in a medium of ethylene dichloride at temperatures below 50°C. produces 1,2-dichloroethane. Two major by-products, 1,1,1-and 1,1,2-trichloroethane, result from substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The other binary systems are modeled with a binary interaction parameter of zero due to the following reasoning: ETC and HCl are expected to only appear in small concentrations, hence the influence on the mixture should be negligible. In addition, experimental results showed that EDC and ETC form an ideal solution [19,20], which is also predicted by the PR EoS.…”
Section: Binary Mixturesmentioning
confidence: 54%
“…The other binary systems are modeled with a binary interaction parameter of zero due to the following reasoning: ETC and HCl are expected to only appear in small concentrations, hence the influence on the mixture should be negligible. In addition, experimental results showed that EDC and ETC form an ideal solution [19,20], which is also predicted by the PR EoS.…”
Section: Binary Mixturesmentioning
confidence: 54%